THE USE OF STORY FACE TO IMPROVE STUDENTS READING COMPREHENSION BY NARRATIVE TEXT - ferra alfyna; Aswir Aswir (JALL (Journal of Applied Linguistics and Literacy), 2021)
The research aimed to analyze Reading  using by story face through visual material, story face. The research was conduct in the class 7.9 of SMPN 03 Tang-Sel. Researcher choose one classes as Experimental class. the use purposive sampling technique by choosing 30 students and conduct pre-test and post-test to gather the researcher data. The experimental class was using story face on learning English. The research lasted for one month and researcher  compared the results of pre-test and post-test through SPSS 22 to conclude the results of research. The experimental class results would be the conclusion of research as this class used Story Face during the lesson. The value of the df t-value is searched based on n=29 with a range of 0,025. Its df t-value is 2,045. Because the t-test value is higher  than the df t-value (5000>2045) h1 is accepted and 0 is rejected, so the learning method is successful in improving student’s reading skill. It means that teaching English by using story face to improve reading comprehension by narrative text was significant.